The Effectiveness of Scaffolded Reading Experience In Teaching Reading Viewed from Students Reading Anxiety - Maximilian, Aksendro (Lentera: Jurnal Ilmiah Kependidikan, 2016)
Scaffolded Reading Experience (SRE) is a set of pre-reading, during-reading, and post-reading activities which is specifically designed to assist the students in successfully reading, understanding, and enjoying the English text. The objectives of the research were to identify: (1) whether SRE is more effective than Direct Instruction (DI) to teach reading; (2) whether students who have low reading anxiety have better reading ability than those who have high reading anxiety; and (3) whether there is an interaction effect between teaching methods and studentsâ reading anxiety on the studentsâ reading ability. The research method used in this research was experimental method. The population of this research was the tenth grade students of SMKN 6 Surakarta, Central Java. The sample of the research was X Pm 1 and X Pm 2. Each of them consisted of 30 students. The students in X Pm 2 were as experimental class who were taught using scaffolded reading experience and the students in X Pm 1 were as control class who were taught using direct instruction. The data were in the form of quantitative data and they were taken from a test. They were the scores of studentsâ reading test after having eight times treatments for each class. The researcher analyzed the data using ANOVA or analysis of variance and Tukey test. Based on the result of data analysis, the research findings are: (1) SRE is more effective than direct instruction to teach reading; (2) the students who have low reading anxiety have better reading skill than the students who have high reading anxiety; and (3) there is an interaction effect between teaching methods (SRE and DI) and studentsâ reading anxiety on the studentsâ reading ability.